Effects of Presentation Modes of Computer Assisted Instruction (CAI) on Learners' Acquisition of Design Skills in Fine Arts - Badru, Folasade Mardlyya Idowu (2015)
The study investigated the effectiveness of problem-solving, and drill and practice modes of Computer Assisted Instruction (CAI) on the acquisition of design skills in Fine Arts. I t also examined learners' attitude towards the use of CAI in the teaching of Fine Arts. This was with a view to providing an intervention strategy for improving the performance of students in Fine Arts.